Laboratory biomarkers or imaging in the diagnostics of rheumatoid arthritis? - Šenolt, Ladislav (BioMed Central, 2014)
Rheumatoid arthritis (RA) is a common autoimmune disease in which a heterogeneous course and different pathogenic mechanisms are implicated in chronic inflammation and joint destruction. Despite the diagnostic contribution of anti-citrullinated protein/peptide antibodies (ACPAs) and rheumatoid factors, about one-third of RA patients remain seronegative. ACPAs belong to a heterogeneous family of autoantibodies targeting citrullinated proteins, including myelin-basic protein, several histone proteins, filaggrin and fibrin, fibrinogen or vimentin. In addition to ACPAs, antibodies directed against other post-translationally modified-carbamylated proteins (anti-CarP) were detected in up to 30% of ACPA-negative patients. Using phage display technology, further autoantibodies were recently discovered as candidate biomarkers for seronegative RA patients. Furthermore, in clinical practice, ultrasound may reveal subclinical synovitis and radiographically undetected bone erosions. To improve diagnostic certainty in undifferentiated arthritis and seronegative patients, ultrasound imaging and several new biomarkers may help to identify at risk patients and those with early disease. In this commentary we summarize recent advances in joint ultrasound and future potential of serological biomarkers to improve diagnosis of RA.